PENGARUH PENGEMBANGAN KARIR DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI DI DINAS PEKERJAAN UMUM KOTA PALU - Gandi, Gandi (Katalogis, 2018)
The purposes of this study were: (1) To determine and analyze the influence of career development partially on employee satisfaction at Palu City Department of Public Works; (2) To determine and analyze the influence of organizational climate partially on employee satisfaction at Palu City Department of Public Works; and (3) To determine and analyze the influence of career development and organizational climate simultaneously on employee satisfaction at Palu City Department of Public Works. The type of this research was descriptive and verificative with survey, while the process of this research was quantitative with associative causal approach, namely quantitative research that aims to determine the causal relationship among the three variables, which serves to explain, predict, and control a symptom, with correlation and regression analysis. The samples of this research amounted to 86 respondents out of the researcher,Â the Head of, and the Secretary of Palu City Department Public Works using saturated sampling technique (census), i.e. the sampling technique that makes the entire population to become samples (Sugiyono, 2007: 65). Data were analyzed using multiple linear regression analysis with the results showed that the career development variable significantly influenced employee performance with tcount amounting to 4.934 > t-table at 2,000 or the Sig-t of 0,000 < Î± value of 0.05; the organizational climate significantly influence employee performance with tcount 5.333 >Â t-table of 2,000 or the Sig-t of 0,000 < Î± value of 0.05; and the variables of career development and organizational climate simultaneously had significant influence on employee performance, with Fcount value of 68.401 > F-table at 2.37 or the Sig-F of 0.000 < Î± value of 0.05.